Inhabited or Uninhabited? Pitfalls in the Interpretation of Possible Chemical Signatures of Extraterrestrial Life - Fox, Stefan; Strasdeit, Henry (Frontiers in Microbiology, 2017)
The “Rare Earth” hypothesis―put forward by Ward and Brownlee in their 2000 book of the same title―states that prokaryote-type organisms may be common in the universe but animals and higher plants are exceedingly rare. If this idea is correct, the search for extra-terrestrial life is essentially the search for microorganisms. Various indicators may be used to detect extant or extinct microbial life beyond Earth. Among them are chemical biosignatures, such as biomolecules and stable isotope ratios. The present minireview focuses on the major problems associated with the identification of chemical biosignatures. Two main types of mis-interpretation are distinguished, namely false positive and false negative results. The former can be caused by terrestrial biogenic contaminants or by abiotic products. Terrestrial contamination is a common problem in space missions that search for biosignatures on other planets and moons. Abiotic organics can lead to false positive results if erroneously inter-preted as biomolecules, but also to false negatives, for example when an abiotic source obscures a less productive biological one. In principle, all types of putative chemical biosignatures are prone to misinterpretation. Some, however, are more reliable (“stronger”) than others. These include: (i) homochiral polymers of defined length and sequence, comparable to proteins and polynucleotides; (ii) enantiopure compounds; (iii) the existence of only a sub¬set of molecules when abiotic syntheses would produce a continuous range of molecules; the proteinogenic amino acids constitute such a subset. These considerations are particularly important for life detection missions to solar system bodies such as Mars, Europa and Enceladus.